2009
DOI: 10.1248/yakushi.129.435
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Cerebral Protection of Digoxin against Ischemia/Reperfusion Injury in Mice

Abstract: The present study was designed to investigate the possible neuroprotective eŠect of digoxin induced pharmacological preconditioning (PP) and its probable mechanism. Bilateral carotid artery occlusion (BCAO) of 17 min followed by reperfusion for 24 h was employed to produce ischemia and reperfusion (I/R) induced cerebral injury in male swiss albino mice. Cerebral infarct size was measured using triphenyltetrazolium chloride staining. Memory was assessed using elevated plus maze test. Degree of motor incoordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
3
13
0
Order By: Relevance
“…We therefore used the MWM test to assess memory, and assessed motor coordination via the rota-rod test, inclined beam walk test, and lateral push test. Our model of global cerebral ischemia and reperfusion increased infarct size and impaired memory as well as motor coordination, consistent with other reports Rehni et al, , 2008aRehni et al, , 2008bPateliya et al, 2008;Kaur et al, 2009aKaur et al, , 2009b. However, milrinone, a phosphodiesterase III inhibitor (Baim et al, 1983), given 24 h prior to global cerebral ischemia, dose dependently reduced infarct size and improved memory and motor coordination.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We therefore used the MWM test to assess memory, and assessed motor coordination via the rota-rod test, inclined beam walk test, and lateral push test. Our model of global cerebral ischemia and reperfusion increased infarct size and impaired memory as well as motor coordination, consistent with other reports Rehni et al, , 2008aRehni et al, , 2008bPateliya et al, 2008;Kaur et al, 2009aKaur et al, , 2009b. However, milrinone, a phosphodiesterase III inhibitor (Baim et al, 1983), given 24 h prior to global cerebral ischemia, dose dependently reduced infarct size and improved memory and motor coordination.…”
Section: Discussionsupporting
confidence: 92%
“…PP can be elicited by receptor agonists for adenosine, aaa-adrenergic, bradykinin, calcitonin gene related peptide (CGRP), opioid receptors (Schulz et al, 1998(Schulz et al, , 2001Rehni et al, 2008b) and ryanodine receptors (Kaur et al, 2009b). We also showed (Rehni et al, 2008b;Kaur et al, 2009b), as did others (Zhao et al, 2007), that pharmacological preconditioning exerts beneficial effects on memory dysfunction associated with cerebral ischemia/reperfusion injury.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our chemical screen revealed cardiac glycosides as the most potent inhibitors of autotic cell death, and we found that they inhibited both autophagy and autotic cell death in the setting of starvation, autophagy-inducing peptide treatment, and neonatal hippocampal hypoxic-ischemic injury. The mechanism of action appears to be inhibition of the target of cardiac glycosides, Na + , K + -ATPase, as we observed similar effects with Na Previous studies have shown that neriifolin and other cardiac glycosides reduce cerebral infarct size in rodent cerebral hypoxia-ischemia models (18,24,25); however, their mechanism of neuroprotection has been unknown. Our observations suggest that inhibition of autophagy and autophagy-dependent death pathways may be a central mechanism of cardiac glycosidemediated neuroprotection.…”
Section: S6csupporting
confidence: 80%
“…A previous chemical screen to identify compounds that provide neuroprotection in a mouse brain slice-based model for ischemic stroke revealed neriifolin as a strong hit, and whole-animal studies have shown that neriifolin and other cardiac glycosides provide neuroprotection in neonatal models of cerebral hypoxia-ischemia (18,24,25). Given these observations, coupled with our findings described above that rat hippocampal CA3 region neurons die by autosis following hypoxia-ischemia, we evaluated whether neriifolin could protect neonatal rats against cerebral hypoxia-ischemia and reduce autosis in the hippocampal region CA3.…”
Section: S6cmentioning
confidence: 99%